Does involving volunteers in the provision of palliative care make a difference to patient, family, and unpaid carer wellbeing and service use? A systematic review - Simone Willis; Charlotte Simpson-Greene; Sabine Best; Sharon Paradine; Briony F Hudson (Palliative Medicine, 2026)
Background: Volunteering is a recognised component of palliative and end-of-life care. The impact of volunteering on palliative care volunteers and their role in specific settings has been reviewed. The impact of volunteers is becoming increasingly relevant in light of the growing demand for palliative care internationally. Aim: Explore the roles and impact of volunteers in palliative care on the wellbeing, mental health, physical health, satisfaction with care, and service use of patients and unpaid carers. Design: Mixed studies systematic review. Protocol registration PROSPERO: CRD42024560700. Data sources: The following databases were searched from 2013 to 2025: AMED, CINAHL, Embase, PsycINFO, HMIC, Web of Science, ProQuest Dissertations and Theses, International Biography of Social Sciences, Cochrane Library. Eligible studies included adults with a terminal illness, their family members or unpaid carers participating in volunteering interventions. Critical appraisal was conducted using Joanna Briggs Institute tools. Results: Twenty-nine reports relating to 24 studies were included. Volunteering roles included peer support, befriending, information provision, arts-based interventions, and practical support. Volunteering interventions positively impacted patients’ hedonic wellbeing, quality of life, and mental health. For eudaimonic wellbeing, quantitative data demonstrated mixed results, while qualitative studies suggested improved social connection. For unpaid carers, there was limited quantitative evidence of impact on wellbeing. Qualitative data indicated interventions were beneficial in supporting advocacy and were well received. Conclusions: Qualitative data indicated volunteering interventions were well received by patients and unpaid carers. Quantitative studies were limited by small sample sizes but demonstrated positive trends. Little evidence that volunteering was associated with harm.